2009
DOI: 10.1016/j.pursup.2009.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Capabilities exchange through business interaction: An empirical investigation of a client–IT supplier relationship

Abstract: a b s t r a c tThis article focuses on the opportunities for capabilities exchange within a specific business-to-business context: the relationship between a client and an information technology (IT) supplier. Research on the features of this type of relationship, although fairly extensive, has focused on IT implementation issues, relationship between IT resources, organisation performance and competitive advantage, IT outsourcing relationships and definition of IT capabilities. However, our understanding of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…To increase the utilisation of IT and digitality in business collaborations, previous studies have focused on the relationships between clients and digital service suppliers, which include for example IT outsourcing relationships (Goo et al 2007) and relationships between buyers and digital service suppliers (Kishore et al 2003). Brito and Nogueira (2009) showed that in the relationships between buyers and digital service suppliers, IT resources from both parties are exchanged and combined, thus improving their related capabilities. Further, Nudurupati, Tebboune, and Hardman (2016) studied PMS in digital economies and suggested that companies need to evaluate their performance in collaborative and social networks and on social media, instead of measuring performance only internally.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…To increase the utilisation of IT and digitality in business collaborations, previous studies have focused on the relationships between clients and digital service suppliers, which include for example IT outsourcing relationships (Goo et al 2007) and relationships between buyers and digital service suppliers (Kishore et al 2003). Brito and Nogueira (2009) showed that in the relationships between buyers and digital service suppliers, IT resources from both parties are exchanged and combined, thus improving their related capabilities. Further, Nudurupati, Tebboune, and Hardman (2016) studied PMS in digital economies and suggested that companies need to evaluate their performance in collaborative and social networks and on social media, instead of measuring performance only internally.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…However, organisations are also social entities, and business relationships develop in interactions among the individuals and groups of employees at different departments of the co-operating firms (Brennan and Turnbull, 1999;Cousins et al, 2006;Cunningham and Turnbull, 1982). Social exchange is important in building long-term relationships, and may exist between individuals even without service or product exchange (Brito and Nogueira, 2009;Ford et al, 2010;Håkansson, 1982;Price and Arnold, 1999). Networks of social relationships may also develop a life of their own, even when they were initially established for task-related activities (Marschan et al, 1996).…”
Section: Interpersonal Interaction and Social Capital In Business Relationshipsmentioning
confidence: 99%
“…In this sense, affective conflict is not conducive to decision-making and therefore makes it difficult for the green partnership to work as planned. In interorganizational contexts, affective conflict prevents collaborating partners from (1) identifying, absorbing, and applying external information (Meier, 2011); (2) generating creativity and quality of decision-making (Parayitam et al, 2010); and (3) extending their capabilities and resources beyond the scope of the organization (Brito and Nogueira, 2009). Affective conflict will therefore have a dysfunctional effect on green product innovation.…”
Section: Conflicts and Green Product Innovationmentioning
confidence: 99%